Superconductores de alta temperatura crítica a base de hierro (2009)
The discovery in early 2008 of a new family of superconductors with a Tc~26K in an iron compound and fluorine doped, LaO1-xFxFeAs, has revived interest in the search for superconducting materials with high critical temperature. The discovery has led to an accelerated study of superconducting properties and many other physical properties, resulting in obtaining new compounds with critical temperatures between 26 - 55 K. In this article it is intended to summarize the main physical and chemist characteristics of this family and related compounds.